Genome-wide identification and characterization of an amino acid permease gene family in Nicotiana tabacum. Issue 60 (2nd August 2017) - Zhao, Yingying; Xu, Yalong; Wang, Zhong; Zhang, Jianfeng; Chen, Xia; Li, Zhengfeng; Li, Zefeng; Jin, Lifeng; Wei, Pan; Zhang, Lin; Zhang, Xiaoquan; Wang, Ran; et al.
Abstract : The amino acid permease (AAP) protein family is an important class of amino acid transporter. Abstract : The amino acid permease (AAP) protein family is an important class of amino acid transporter. However, little information about this gene family is available in tobacco. Here, a total number of 15, 7, and 6 full-length putative AAP genes have been identified in the genomes of Nicotiana tabacum and progenitors of modern tobacco, Nicotiana sylvestris and Nicotiana tomentosiformis, respectively. We performed a multiple analyses of the AAP gene family in tobacco and reported data including phylogenetic relationships, gene structures, predicted protein structures and information about conserved motifs. These tobacco AAP family members shared high levels of similarity in their nucleotide and amino acid sequences. The gene structures of the NtAAP loci were all separated by introns. Phylogenetic analyses indicated that these AAP genes were clustered into three groups. We also performed expression profiling analyses of the NtAAP genes in various tobacco tissues/organs using quantitative PCR. The differential expression patterns of the NtAAP genes suggested that the family members might have different biological functions in tobacco plants. To study the function of NtAAP2-2, its coding sequence was cloned and overexpression/RNA interference vectors were constructed and these vectors were transformed into tobacco. Compared with wild-type tobacco, the contents of Glu, Gln, Asp and Asn were found to change in the transgenic tobacco leaves, indicating that NtAAP2-2 was involved in the transportation of Glu, Gln, Asp and Asn in tobacco. Our results can serve as fundamental research for future evolutionary and functional characterization studies of the AAP genes in tobacco.